Study of Xylose as Product Inhibitor in Xylanase from Aspergillus niger, Basillus subtilis, and Tricodherma reesei: Insilico and Experimental Review Approach - Sigit Hadiantoro; Dyah Ratna Wulan; Amiruz Zahidin; Yanty Maryanty (The Journal of Pure and Applied Chemistry Research, 2022)
Bioinformatics is useful for solving molecular biology problems computationally. This computational chemistry has the advantage of being safe, free from chemical waste, secure, cost-effective, and can shorten research time. The issues that arise can be in the form of basic things such as solving enzyme mechanisms, protein metabolism, or identifying microbes. Degradation of the xylanase enzyme using some microorganisms. They are Aspergillus niger, Bacillus subtilis, and Thricodherma reesei on lignocellulose bonds. Lignocellulose consists of lignin, cellulose, and hemicellulose. Cellulose and hemicellulose can have used to produce new products such as bio-based products. To predict the optimum conditions for this enzymatic reaction has used bioinformatics applications has used through substrate enzymes obtained from protein data banks. The purpose of this study was to determine the optimum conditions for obtaining xylanase enzymes from the microorganisms Aspergillus niger, Bacillus subtilis, and Thricodherma reesei by bioinformatics (in silico). This research was conducted in bioinformatics using a database from the RCSB Protein Data Bank and PubChem. The programs used to see the interaction between substrate enzymes in this study are PyMol, PyRx, and LigPlot. The best conditions based on the results of bioinformatics simulations will form the basis for producing xylanases on a laboratory scale. In this study, the results of interaction data between Bacillus subtilis and D-xylose, which have a binding affinity value of -5.2 kcal/mol.  Aspergillus niger with D-xylose, which has a binding affinity value of -5.1 kcal/mol, Tricodherma reesei with D-xylose, which has binding affinity value -4.3 kcal/mol.